Peran Kelompok Tani Terhadap Kapasitas Petani Padi Sawah di Desa Lamomea Kecamatan Konda Kabupaten Konawe Selatan - Amelia Amelia; Sukmawati Abdullah; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2021)
This study aims: 1) Knowing the role of farmer groups on the capacity of rice farmers (2) Knowing the capacity of farmers in lowland rice farming (3) Knowing the relationship between farmer groups and farmer capacity. rice fields in Lamomea Village, Konda District, South Konawe Regency. This research was conducted from April to 2021. The sampling technique used was the census method, and the data analysis used was the class interval formula and Spearman Rank Correlation. The results of the farmer group research in Lamomea Village, Konda District, South Konawe Regency have been carried out quite well, whereas a learning class, as a vehicle for cooperation and production units, there are 23 (95.83%) respondents. The capacity of Rice Paddy Farmers in Lamomea Village, Konda District, South Konawe Regency has been carried out sufficiently, which is possible from the technical ability, problem-solving ability, adaptability, and ability that has been carried out sufficiently by farmers in this research area as many as 23 (95), 8%) respondents. The role of farmer groups on the capacity of lowland rice farmers there is a very close relationship between the role of farmer groups and the capacity of rice farmers with a correlation coefficient value of 0.919 with a significant level of 0.000. Where the increase in both the role of farmer groups will increase the capacity of lowland rice farmers.